(untitled) (Research, Society and Development, 2020)
The objective was to analyze the importance of the father’s participation during the gestational period, emphasizing the challenges and implications experienced by him. A bibliographic search was carried out using the integrative review method, the study was carried out through a search in the Virtual Health Library (VHL) known for having a large collection of national and international scientific publications, with a search in the databases BDENF, LILACS and through from the Us National Library of Medicine (PUBMED). For the choice of articles, the following descriptors were used: "Pregnancy", "Prenatal Care" and "Father" accompanied by the Boolean operator AND. In total, 493 articles were found, of which, applied the inclusion criteria, 90 were selected for reading the titles and abstract. After careful reading, 14 articles were selected that met the research objective to compose the work. The results of the study highlighted the challenges and implications of father involvement in prenatal care. In addition, the study also exposed the benefits for both mother, father and baby, of paternal participation in prenatal consultations. It is concluded that there are several cultural, socioeconomic, personal and health system-related barriers that hinder and decrease the father’s participation in the gestational process. Being present provides personal growth and maturation of men and can change their perspective of life, showing affection, solidarity and close to intimacy, changing habits and social values.